Loculosulcatispora thailandica gen. et sp. nov. (Sulcatisporaceae), saprobic on woody litter in Thailand - Ren, Guang-Cong; Wanasinghe, Dhanushka N.; Wei, De-Ping; Monkai, Jutamart; Yasanthika, Erandi; Gui, Heng; Mortimer, Peter E.; Xu, Jian-Chu; Hyde, Kevin D. (Phytotaxa, 2020)
A new monotypic coelomycetous genus, Loculosulcatispora (type species L. thailandica) is introduced in Pleosporales from woody litter in Thailand. Phylogenetic analysis of combined non-translated loci (SSU, LSU, ITS) and protein-coding regions (tef1-α, rpb2) shows the genus is a distinct lineage in Sulcatisporaceae. Loculosulcatispora is distinguished from other genera in the family, by having 1-celled, oblong, hyaline, smooth-walled conidia with guttules. Comprehensive morphological descriptions and illustrations are provided for the new genus and species.